Speech and morality : on the metaethical implications of speaking - Cuneo, Terence, 1969- (Oxford University Press, 2014)
Terence Cuneo presents a new argument for moral realism. According to the normative theory of speech, speech acts are generated by an agent's altering her normative position with regard to her audience. In doing so she takes on rights and responsibilities, some of which are moral and objective: these are a necessary condition of speech.